2014
DOI: 10.1021/ie502683r
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Surface Chemistry of Activated Carbon on the Activity of Gold/Activated Carbon Catalyst in Acetylene Hydrochlorination

Abstract: The main goal of this work is to study the relationship between the surface chemistry of activated carbon (AC) and the performance of respective gold-supported catalysts in the acetylene hydrochlorination. For this purpose, a set of modified activated carbons with different levels of oxygenated groups on the surface, but with no major differences in their textural parameters, was prepared. A strong effect of the surface chemistry of activated carbon on the Au/AC catalytic activity was observed. Comparison of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 47 publications
1
43
0
Order By: Relevance
“…Dai et al 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 the surface of the active carbon, and the carboxylic group was responsible for the reduction of Au 3+ . After the pretreating of active carbon with an HNO 3 solution, the nitrogen species could also anchor the Au 3+ cations and enhance the adsorption of the HCl reactants [41]. Hutchings et al discussed the effect of the solvent aqua regia on the activity of the Au/C catalyst (Fig.…”
Section: Au-based Catalystsmentioning
confidence: 99%
“…Dai et al 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 the surface of the active carbon, and the carboxylic group was responsible for the reduction of Au 3+ . After the pretreating of active carbon with an HNO 3 solution, the nitrogen species could also anchor the Au 3+ cations and enhance the adsorption of the HCl reactants [41]. Hutchings et al discussed the effect of the solvent aqua regia on the activity of the Au/C catalyst (Fig.…”
Section: Au-based Catalystsmentioning
confidence: 99%
“…Although the new surface oxygen groups appeared to promote the dispersion of a ruthenium precursor deposited from solution, the authors concluded that, subsequently, oxygen states weakened the ruthenium nanoparticle/support interaction. 3 Xu et al 4 studied this issue for gold, using concentrated HNO 3 solutions, (65 wt% at 90 C for 6 h) followed by thermal treatment to inuence the functional groups available at the surface. They concluded that phenol, ether, and carbonyl groups stabilise the gold catalyst and enhance activity but could not distinguish between the different groups or their mode of action.…”
Section: Introductionmentioning
confidence: 99%
“…For Au(aq)/AC catalyst (Fig. 8c), an identifiable hydrogen consumption peak in the range 450-800°C can be attributed to reduction of the oxygen-containing groups on the carbon surface [61,62]. The presence of the oxygen-containing groups is consistent with the oxidizing effect of the aqua regia on the AC surface.…”
Section: The Valence and Reducibility Of Au Species Before And After mentioning
confidence: 52%